Savonarola’s Middlemen: The Buonomini di San Martino in the Florentine Religious Revival of the 1490s - Walsh, Martin (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2023)
In his program for reforming Florence Dominican friar Girolamo Savonarola not only staged his famous “Bonfires of the Vanities,” but also directed his congregations to increase their alms giving, specifically for the “shamefaced poor,” respectable families in need but ashamed to beg. Not allowed by his order to administer such funds directly, Savonarola instructed that they be deposited with the Buonomini di San Martino, a confraternity specifically devoted to relieving the “shamefaced poor.” With these responsible middlemen in place, Savonarola would thus avoid any charges of financial impropriety. The alms collectors during Carnival seasons 1496 to 1498 were Savonarola’s fanciulli, youths reformed of their Carnival hijinks. The ceremonial depositing of alms at the oratory in Piazza San Martino would achieve a secondary goal for Savonarola, the sanctification of a profane performance space, the piazza being a prime venue for “bench singers” and other popular entertainers.